Dancing in Milan - Masini, Beatrice; Translated by Laura Watkinson (London Piccadilly, 2010)
"At the start of summer, Zoe hears some wonderful news - she's been chosen to take part in a dance course in Italy! There's only one problem. Laila is going too. When Zoe and Laila are together, sparks usually fly, so how will they cope spending so much time together."--Publisher.
Keywords: Ballerinas -- Ballet dancing -- Dance schools